(untitled) (Progressive Agriculture, 2013)
Two potato varieties, Cardinal and Heera, were used to optimize the Agrobacterium-mediated genetic transformation system in potato for abiotic stress tolerance. MS medium supplemented with different concentrations and combinations of NAA and BAP were used to obtain callus induction from leaf explants of potato cv Cardinal and Heera. Maximum percentage of callus induction (95.83%) was observed in MS medium supplemented with 4 mg/L NAA and 2 mg/L BAP. The highest callusing was found in Cardinal and the lowest in Heera. Calluses were inoculated with Agrobacterium tumefaciens strain LBA4404 (pB1121) carrying CIPK sense gene, selectable marker gene nptII gene conferring resistance to kanamycin and the GUS reporter gene. Both the varieties were found GUS positive after inoculation and selection. Cardinal had maximum percentage of survived callus (25%) on selection media. Stable intregration and expression of the transgenes were confirmed by GUS histochemical assay. DOI: http://dx.doi.org/10.3329/pa.v19i2.16919 Progress. Agric. 19(2): 37 - 43, 2008